2016
DOI: 10.1109/jlt.2016.2567479
|View full text |Cite
|
Sign up to set email alerts
|

Signal Overlap for Elastic Optical Networks

Abstract: In Elastic Optical Networks (EONs), advanced transmission techniques based on coherent detection strategies have been proposed and exploited to provide high flexibility in resource allocation. So far, these techniques have assumed the constraint of each optical signal being transmitted along a dedicated frequency slot, by carefully avoiding frequency overlap with other optical signals.In this study, an overlap technique, that enables uncorrelated optical signals to be superimposed along the same spectrum resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 29 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In Reference [12], the transmission capability of the Signal Overlap method is evaluated based on performance and biterror rate. It is demonstrated that the superimposition of uncorrelated optical signals is feasible in the same spectrum resources.…”
Section: Related Researchmentioning
confidence: 99%
“…In Reference [12], the transmission capability of the Signal Overlap method is evaluated based on performance and biterror rate. It is demonstrated that the superimposition of uncorrelated optical signals is feasible in the same spectrum resources.…”
Section: Related Researchmentioning
confidence: 99%
“…In [62], the Signal Overlap technique is presented and evaluated according to its performance and bit-error rate, concerning its transmission capability. This technique allows the superimposition of uncorrelated optical signals in the same spectrum.…”
Section: Selenementioning
confidence: 99%